Drosophila chk2 plays an important role in a mitotic checkpoint in syncytial embryos. - Xu, J.; Du, W. (FEBS Letters, 2003)
Drosophila chk2 (Dmchk2, also called Dmnk) plays a crucial role in the DNA damage response pathway mediating cell cycle arrest and apoptosis [Xu et al., FEBS Lett. 508 (2001) 394-398; Peters et al., Proc. Natl. Acad. Sci. USA 99 (2002) 11305-11310]. In this study, the role of Dmchk2 in early embryogenesis was investigated. In the absence of Dmchk2 function, abnormal nuclei accumulate in the cortex of the syncytial embryo. We show that the abnormal nuclei result from a failure of chromosome segregation probably due to damaged or incomplete replicated DNA. Importantly, this Dmchk2 phenotype is partially suppressed by reducing the gene dosage of polo or stg. As Polo-like kinase was shown to colocalize and coimmunoprecipitate with Chk2 [Tsvetkov et al., J. Biol. Chem. 278 (2003) 8468-8475] in mammals, these observations suggest that polo might be a key target of Dmchk2 in regulating mitotic entry in response to DNA damage or replication block.